Molecular Characterization and Phylogenetic Analysis of Chicken Infectious Anaemia Virus in Commercial Poultry Flocks in Andhra Pradesh - Kumar K, Pavan; Pushpa R N, Ramani; A R, Supriya; G, Saikumar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Chicken infectious anaemia (CIA) is a significant economic concern in the poultry industry, particularly among young chicks. It is characterized by inadequate weight gain, anaemia, immunosuppression, and production loss. The study aimed to identify chicken anaemia viruses (CAVs) in suspected commercial poultry flocks and molecular characterization of the VP1 gene of circulating CAVs, along with phylogenetic analysis of the VP1 gene. Throughout the study, samples were obtained from 47 birds in nine commercial poultry flocks during necropsy. Tissue samples including the thymus, bone marrow, liver, and spleen, were collected in phosphate buffer saline (PBS) and subjected to PCR targeting VP1 gene, resulting in the amplicon size of 454 bp. Among 47 samples 40 were found positive for the VP1 gene. The DNA from four different farms, tested positive, was sent for sequencing of the VP1 gene. Phylogenetic analysis based on nucleotide sequence alignment revealed that CAV isolates from Nuzividu region clustered with isolates from China and the remaining three CAV isolates did not form any group with the already known genotypes. Furthermore, to understand the spread of the disease and help to develop effective control and prevention strategies, the detailed information about the specific circulating CAV strains is needed.